Durable HIV RNA resuppression after virologic failure while remaining on a first‐line regimen: a cohort study. Issue 2 (3rd December 2013) - Hoffmann, Christopher J.; Charalambous, Salome; Grant, Alison D.; Morris, Lynn; Churchyard, Gavin J.; Chaisson, Richard E.
Summary Adherence interventions are a recommended strategy to salvage failing antiretroviral therapy without regimen change. We assessed the durability of resuppression when using this approach. Of 300 patients who resuppressed on the same regimen (41% of all those with virologic failure), 148 (45%) remained suppressed during follow‐up for a median of 2.4 years (interquartile range [IQR]: 1.1, 4.0). Resuppression can be durable following viraemia without a switch in antiretroviral therapy regimen.